Pengembangan Aplikasi Manajemen Pengawasan Proyek Konstruksi berbasis Android pada Perusahaan AMF-Haq Engineering and Consultant - Muchibbuddin Abas; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
AMF-Haq Engineering and Consultant company is a small-medium enterprise that focuses on construction sector. The issue that happened in that company is in project supervising and controlling sector such as the limitation of the owner of the company in giving information straight away related to project plan to the project workers, less of efectivity in monitoring the project development in different locatio, and the process of reporting progress in every project is ineffecient. The aim of this research is to develop an application that makes the project supervising and planning process easier that applied by the company. The aplication that will be developed is expected to be able to improve the effectivity and efficiency of the process of planning, supervising and reporting project progress that has been done by the company. This application will be developed on platform mobile Android using framework react-native by using System Development Life Cycle ( SDLC) method, waterfall speciment. On this research, be achieved analisis result on the application need such as 48 functional needs and nonfunctional need on compability application aspect. From the testing that has been done by researcher, be achieved valid result for unit testing using white box testing method the entire test path. In the validation test using black box testing method, be achived valid value to entire test cases, then in compability test shows that the system can be used well on 2 kinds of mobile phones and 5 types of operation system in Android.